1995
DOI: 10.1093/oxfordjournals.aje.a117521
|View full text |Cite
|
Sign up to set email alerts
|

Public Drinking Water Contamination and Birth Outcomes

Abstract: The effects of public drinking water contamination on birth outcomes were evaluated in an area of northern New Jersey. After excluding plural births and chromosomal defects, 80,938 live births and 594 fetal deaths that occurred during the period 1985-1988 were studied. Information on birth outcome status and maternal risk factors was obtained from vital records and the New Jersey Birth Defects Registry. Monthly exposures during pregnancy were estimated for all births using tap water sample data. Odds ratios of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
319
5
11

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(343 citation statements)
references
References 29 publications
8
319
5
11
Order By: Relevance
“…A number of studies have found statistically significant positive associations between THMs and neural tube defects (NTDs), one of the most studied groups of congenital anomalies (Bove et al 1995;Klotz & Pyrch 1999;Dodds & King 2001), whereas other studies have not found statistically significant associations (Dodds et al 1999;Magnus et al 1999;Källen & Robert 2000;Hwang et al 2002;Shaw et al 2003;Nieuwenhuijsen et al 2008) (table 2). Klotz & Pyrch (1999) found a statistically significant association between total THM (TTHM) levels in the water and NTDs, but not with levels of haloacetonitriles and HAA.…”
Section: (B) Reproductive Outcomesmentioning
confidence: 99%
“…A number of studies have found statistically significant positive associations between THMs and neural tube defects (NTDs), one of the most studied groups of congenital anomalies (Bove et al 1995;Klotz & Pyrch 1999;Dodds & King 2001), whereas other studies have not found statistically significant associations (Dodds et al 1999;Magnus et al 1999;Källen & Robert 2000;Hwang et al 2002;Shaw et al 2003;Nieuwenhuijsen et al 2008) (table 2). Klotz & Pyrch (1999) found a statistically significant association between total THM (TTHM) levels in the water and NTDs, but not with levels of haloacetonitriles and HAA.…”
Section: (B) Reproductive Outcomesmentioning
confidence: 99%
“…Most previous studies on the association of DBPs with birth defects also used routinely collected THM data and a variety of approaches were used for their exposure assessment (Nieuwenhuijsen et al, 2000a, b). For example, for a study in New Jersey (USA) Bove et al (1995) took quarterly averages of total THM data collected at least four times each quarter. Unfortunately, our, and other studies, had far fewer THM measurements available for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A common approach has used information on birth certificates to identify maternal residence and exposure to some potential confounders ( Bove et al, 1995;Gallagher et al, 1998;Dodds et al, 1999 ). Exposure assessment has typically been based on the concentration of total trihalomethanes in the study subject's municipal water source.…”
Section: Introductionmentioning
confidence: 99%